Growth and yield performance of cabbage (Brassica oleracea var. capitata L.) as influenced by doses of nitrogen and zinc fertilizers - Sultana, Afrin; Altaf-Un-Nahar, Most; Siddika, Mst Ayesha; Karim, Md Rezaul (Fundamental and Applied Agriculture, 2023)
The present study was conducted at the Horticulture Farm of the Department of Horticulture, Bangladesh Agricultural University during the period from October 2022 to February 2023 to assess the effects of different doses of nitrogen (N) and zinc (Zn) on growth and yield of cabbage. The two-factor experiment was laid out in Randomized Complete Block Design (RCBD) with three replications. The first factor was nitrogen having four doses of N, such as N0 =0 kg ha−1,N1 =100 kg ha−1, N2 =150 kg ha−1 and N3 = 200 kg ha−1, and four doses of Zn, namely Zn0 = 0 kg ha−1, Zn1= 1.5 kg ha−1, Zn2 = 2.0 kg ha−1, Z3 = 2.5 kg ha−1. Significant variations were noted due to the application of different doses of N and Zn fertilizers in respect of all the growth and yield traits studied. Application of N at 200 kg ha−1 contributed the best outcomes on plant height (32.72 cm), number of leaves per plant (47.86), gross yield per hectare (69.99 t), marketable yield per hectare (45.98 t) and the lowest yield per hectare (64.52 t), the lowest marketable yield per hectare (38.37 t) were obtained from control treatment. The highest level of zinc (2.5 kg ha−1) produced the best results on plant height (32.30 cm), number of leaves (48.26) per plant, gross yield per hectare (78.02 t), marketable yield per hectare (61.62 t) and the lowest gross yield per hectare (59.17 t), lowest marketable yield per hectare (29.40 t) produced from control treatment. The maximum doses of nitrogen and zinc (200 kg ha−1 and 2.5 kg ha−1), respectively showed the best performance on plant height (33.32 cm), number of leaves (49.53) per plant, gross yield per hectare (81.15 t), marketable yield per hectare (65.78 t) and the lowest gross yield per hectare (55.41 t) and marketable yield per hectare (27.28 t) were obtained from the control treatment. The results of this investigation revealed that application of N and Zn enhanced the affects the growth and yield of cabbage. However, further investigation may be carried out with higher doses of N and Zn fertilizers.